Zinc shields against copper phytotoxicity in a contaminated soil - Dubrovina, Tatiana A; Zhikharev, Alexander P; Dovletyarova, Elvira A; Brykova, Ramilla A; Yáñez, Carolina; Neaman, Alexander (Chemosphere, 2024)
While zinc protects plants from copper in hydroponics, its behavior in soil remains unclear. We investigated the potential of zinc sulfate to protect ryegrass from copper toxicity in contaminated soil. Twelve soil treatments combined varying levels of copper oxide (CuO) and zinc sulfate (ZnSO4). Increasing CuO significantly stunted ryegrass, but adding ZnSO4 mitigated the effects at each CuO level. ZnSO4 had no effect in unpolluted conditions. These results, supported by the Terrestrial Biotic Ligand Model, indicate that zinc competes with copper for binding sites, reducing copper uptake by ryegrass and mitigating its toxicity. Application of zinc sulfate to copper-contaminated soils appears promising for ryegrass growth, although field studies are critical to confirm real-world efficacy.
Keywords: půda; znečištění životního prostředí; Environmental Pollution; Zinc Sulfate; Lolium perenne; jílek; síran zinečnatý; Zinc; Soil; zinek; Lolium; látky znečišťující půdu; Antagonism; Alleviating affect; Protective effect; měď; Soil Pollutants; Copper